(untitled) (East West Medical College Journal, 2025)
Background: Breastfeeding has numerous health advantages for both the mother and the child and is crucial for the growth and development of children. For the first six months of a baby’s life, breastfeeding supplies all the energy and nutrients they require. It also meets up to half or more of a child’s nutritional demands in the second half of the first year and up to a third in the second year. Objective: This study determines the feeding practices and its association with co-morbidities among the infants of working mothers in a selected garments factory of Bangladesh. Methods: This cross sectional study was conducted in a selected Garments Factory in Narayangonj on 267 working mothers having infants aged 0-12 months. After taking consent of the study subjects were enrolled in the study. A detail history was taken regarding breastfeeding practices and complementary feeding as well as co-morbidities. Results: The bulk of infants (58.8%) belonged to the 6–12 month age range. 6.70±2.77 months was found to be the mean age. Male babies made up over half (52.4%) of the total. Of the 267 moms surveyed, 174 (65.2%) reported starting to breastfeed after a period of one to twelve hours, 200 (74.9%) had experience with colostrum feeding, 64 (24.0%) had administered pre-lacteal feeding, and 58 (21.72%) had exclusively breastfed. After 2.9±0.8 months of exclusive breastfeeding, 92 moms (58.6%) began supplemental feeding by the time their babies were 6 months old. Thirty two (50.0%) received honey as a pre-lacteal meal. The majority of 31.58% of newborns received suji, or rice powder, in addition to nursing. In the last six months, 87 (32.58%) infants experienced pneumonia, 45 (16.85%) experienced diarrhea, 43 (16.10%) experienced skin infection, and 19 (7.12%) experienced ear infection. Conclusion: Evidence of incorrect feeding practices among working mothers was found in this study. Their infants developed a variety of related co-morbidities (such as pneumonia, diarrhea, skin infections, and ear infections) as a result of non-exclusive breastfeeding and improper supplemental feeding. EWMCJ Vol. 13, No. 1, January 2025: 28-34